Editors' Choice Communication—Hourglass-Shaped Metal-Filament Switching Device with Multi-Layer (AlOX/TiO2) Oxide Electrolytes. (1st January 2016) - Lim, Seokjae; Woo, Jiyong; Lee, Sangheon; Park, Jaesung; Hwang, Hyunsang
Abstract : This paper proposes using hourglass-shaped metal filaments to improve the ON/OFF resistance ratio and retention characteristics of switching devices used in reconfigurable logic applications. These filaments are obtained by controlling the Cu-ion mobility in multi-layer oxide electrolytes. By adopting an upper AlOX and lower TiO2 electrolyte layers with respectively low and high Cu-ion mobility, we could form hourglass-shaped filaments as a result of suppressed Cu-ion injection and enhanced filament lateral growth. The hourglass-shaped metal filaments induced local Joule heating at the filament constriction, thus accelerating RESET operations. We confirmed that, as a result, Cu/AlOX /TiO2 /W devices show high ON/OFF resistance ratios (>10 6 ) and ∼10-year retention properties at 80°C.